2020
DOI: 10.29121/granthaalayah.v7.i12.2019.307
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Multi-Criteria Decision-Making Analysis for a Warehouse Location Selection Problem: A Case Study

Abstract: The problem of a warehouse location selecting which has a significant impact on logistics costs is an important decision problem based on the best choice of alternatives under multiple conflicting criteria. Multiple-criteria decision-making (MCDM) methods are used as a solution approach for the decision problems including several criteria. In this study, a new stochastic multi-criteria decision-making approach has been developed to solve the warehouse location selection problem (WLSP) in the stochastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Considering literature related to identifying warehouse location, it was found that there were different methods used depending on the purposes and location of the studies. Multiple-criteria decision-making (MCDM) methods and examination of several criteria were used as a solution for a supermarket chain located in Turkey [6]. Fuzzy Analytic Hierarchy Process (FAHP) had been used to select warehouse locations for a global supply chain through a case study in Iran [1] and had been used as a decision support framework for selecting a location and creating a disaster relief network design in Indonesia [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering literature related to identifying warehouse location, it was found that there were different methods used depending on the purposes and location of the studies. Multiple-criteria decision-making (MCDM) methods and examination of several criteria were used as a solution for a supermarket chain located in Turkey [6]. Fuzzy Analytic Hierarchy Process (FAHP) had been used to select warehouse locations for a global supply chain through a case study in Iran [1] and had been used as a decision support framework for selecting a location and creating a disaster relief network design in Indonesia [7].…”
Section: Literature Reviewmentioning
confidence: 99%